Medieval and early modern ceramics in urban and rural Norway as evidence for trade within the Hanseatic world (AmS-Skrifter, 2020)
In Norway, pottery from the fourteenth to seventeenth centuries is always imported and mostly concentrated in the urban centres. The few finds of pottery from this period in a non-urban context can, however, shed light on the spreading of a continental or Hanseatic culture into the periphery of this country. This paper provides a broad overview of archaeological finds of pottery from Bergen and their implications as sources of cultural history. Furthermore, this paper presents various rural and underwater finds of late medieval and early modern pottery in different regions of Norway, along with a discussion of a possible interpretation of the finds as sources for Hanseatic history.